Mesenchymal Stem Cell Conditioned Media Ameliorate Psoriasis Vulgaris: A Case Study. (2nd May 2019) - Seetharaman, Rajasekar; Mahmood, Anjum; Kshatriya, Prashant; Patel, Divyang; Srivastava, Anand
Abstract : Psoriasis, an autoimmune disease, affects a vast number of peoples around the world. In this report, we discuss our findings about a scalp psoriasis suffering patient with a Psoriasis Scalp Severity Index (PSSI) score of 28, who was treated with Mesenchymal stem cell conditioned media (MSC-CM). Remarkably, complete regression was recorded within a treatment period of one month only (PSSI score of 0). A number of bioactive factors like cytokines and growth factors secreted by MSCs in the conditioned medium are very likely to be the principle molecules which play a vital role in skin regeneration. Treatment using MSC-CM appears to be an effective tool for tackling the psoriatic problem and, thus, may offer a new avenue of therapy which could be considered as an alternative approach to overcome the limitations of the cell-based therapy.